Performance Evaluation of an Enhanced Geothermal System in the Western Canada Sedimentary Basin. (October 2019) - Kazemi, A.R.; Mahbaz, S.B.; Dehghani-Sanij, A.R.; Dusseault, M.B.; Fraser, R.
Abstract: Sustainable low-carbon energy resources (e.g., geothermal energy) are important solutions to meet growing energy demand in developed and developing countries. Because of recent advances in drilling and hydraulic fracturing technologies for flow enhancement, Enhanced Geothermal Systems based on hot/warm fluids from deep geological formations have an increasingly interesting potential for power and heat supply. In this paper, a conceptual Sedimentary Enhanced Geothermal System in the Williston Basin is investigated numerically. Thermo-hydraulic and hydro-mechanical coupled models are used to assess the thermal performance and stress evolution of a geothermal doublet system. Using realistic properties of the target area, doublet spacing and recirculation flow rate are studied to evaluate the growth of the heat transfer volume. Introducing a more permeable zone (i.e., a fault or high permeability channel) across the flow path between wells does not shorten the useful reservoir lifetime; in fact, it delays cold front advancement by lateral broadening of the heat transfer domain. As cold water is re-injected into the reservoir in a recirculation approach, large stress changes are generated, and the stress distribution and local stress gradients change with time through combined convective and conductive heat transfer. Although the rock model used represents an unfractured sandstone with negligible permeability sensitivity to effective stress changes, the authors note that for a naturally fractured reservoir the stress changes will have major impacts on flow paths (compressional versus extensional expansion) and hence temperature distributions and heat extraction behavior. Highlights: A Thermo-Hydro-Mechanical numerical simulation of a potential geothermal reservoir, located in the deep sedimentary formations, southeastern Saskatchewan, Canada. Evaluation of long-term (30 years) thermal performance and stress state of a doublet well Enhanced Geothermal System using coupled thermo-hydraulic and hydro-mechanical models. Study of well spacing and recirculation flow rate to assess the growth of heat transfer volume in presence/absence of a highly permeable fault. Define a cold front ratio and its calculation for different hydraulic and geometrical scenarios in a studied doublet geothermal system.